1990
DOI: 10.1111/j.1365-2141.1990.tb04346.x
|View full text |Cite
|
Sign up to set email alerts
|

MDR1 transcript levels as an indication of resistant disease in acute myelogenous leukaemia

Abstract: The expression of the MDR1 gene was studied by Northern blot analysis in leukaemic cell specimens obtained from 74 patients with acute myelogenous leukaemia (AML). No relationship was found between MDR1 RNA levels and FAB type of leukaemia or patient age. Transcript levels tended to be highest in the leukaemic cells of patients with a history of toxic exposure or preleukaemia compared with 'standard risk' patients at diagnosis but the differences were not significant (P = 0.07). Patients whose leukaemic cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1
1

Year Published

1991
1991
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(55 citation statements)
references
References 12 publications
2
51
1
1
Order By: Relevance
“…This multidrug resistance may be reversed or overcome by such agents as calciumchannel blockers, analogs of anthracyclines and vinca alkaloids, steroids and hormonal analogs, cyclosporine analogs, and miscellaneous hydrophobic cationic compounds (3, 18 -20). MDR-1 gene expression in acute leukemias has been documented extensively (15,16,(21)(22)(23) and is rapidly assuming the role of one of the most important mechanisms of drug resistance in this setting (9). These patients typically are resistant to standard myeloid protocol and thus have a poor prognosis (24).…”
Section: Discussionmentioning
confidence: 99%
“…This multidrug resistance may be reversed or overcome by such agents as calciumchannel blockers, analogs of anthracyclines and vinca alkaloids, steroids and hormonal analogs, cyclosporine analogs, and miscellaneous hydrophobic cationic compounds (3, 18 -20). MDR-1 gene expression in acute leukemias has been documented extensively (15,16,(21)(22)(23) and is rapidly assuming the role of one of the most important mechanisms of drug resistance in this setting (9). These patients typically are resistant to standard myeloid protocol and thus have a poor prognosis (24).…”
Section: Discussionmentioning
confidence: 99%
“…Pgp functions, at least in part, as an energy-dependent efflux pump for some hydrophobic chemotherapeutic agents, although its exact functional mechanism is likely to be more complicated (6). MDR1 gene expression is associated with treatment failure in some hematopoietic malignancies, including acute myelogenous and lymphocytic leukemias (2,23,25,35,39,46,47,49,50), the blast crisis phase of chronic myelogenous leukemia (31, 45), and multiple myeloma and non-Hodgkin's lymphoma (14,15,20,41,48). In these malignancies, MDR1 expression occurs more frequently after chemotherapeutic treatment, suggesting a selection for MDR1 ϩ cells and/or acquisition of the MDR1 phenotype in response to tumor progression or antineoplastic exposure (6).…”
mentioning
confidence: 99%
“…We must point out that Ubezio et al (30) and Kato et al (17) found no substantial differences in DNR retention in lymphoblasts from resistant and sensitive patients with leukemia, while Sato et al observed a feable correlation between the mdrl transcription and the clinical data (27). However, the improvements (mainly the use of vrp), could yield a technique able to detect resistant cells.…”
Section: Comparison To Clinical Resultsmentioning
confidence: 87%